Deposition of chromosomal protein HMG-17 during replication affects the nucleosomal ladder and transcriptional potential of nascent chromatin. - Crippa, M P (1993)
A cell-free system from Xenopus eggs was used to study the role of chromosomal protein HMG-17 in the generation of the chromatin structure of transcriptionally active genes. Addition of HMG-17 protein to the extracts, which do not contain structural homologs of the HMG-14/-17 protein family, indicates the protein is incorporated into the nascent template during replication, prior to completion of chromatin assembly. The protein binds to and stabilizes the structure of the nucleosomal core thereby improving the apparent periodicity of the nucleosomal spacing of nascent chromatin. Assembly of HMG-17 into the nascent chromatin structure significantly increased the transcription potential of the 5S RNA gene and satellite I chromatin. Kinetic studies indicate that the increase in transcriptional potential is observed only when HMG-17 is incorporated into nucleosomes during chromatin assembly.